Tenecteplase in large-vessel occlusion with or without thrombectomy: a meta-analysis - Alkhiri, Ahmed; Alamri, Aser F.; Alturki, Fahad; Alonazi, Remas M.; Nguyen, Thanh N.; Al-Ajlan, Fahad S.; Alhazzani, Adel (Frontiers in Neurology, 2026)
BackgroundDespite the growing adoption of Tenecteplase for stroke thrombolysis, key questions such as the role of bridging therapy and extended-window use in large-vessel occlusion (LVO) patients with or without access to endovascular thrombectomy (EVT) remain unresolved.MethodsWe conducted a systematic review of randomized clinical trial (RCT) data involving LVO patients who were treated with or without Tenecteplase. Outcomes were stratified by EVT status, and further subgroup analysis based on treatment window (≤4.5 vs. > 4.5 h) was conducted. Generalized odds ratios (gORs) were used to assess disability reduction by modified Rankin Scale (mRS) shift analysis. Risk ratios (RRs) with 95% confidence intervals (CIs) were calculated for functional independence (mRS 0–2), excellent outcome (mRS 0–1), mortality, and symptomatic intracranial hemorrhage (sICH).ResultsFive studies (2,054 patients) were included. Treatment with Tenecteplase was associated with greater disability reduction (gOR, 1.19; 95% CI, 1.06–1.34), more excellent outcome (RR, 1.21; 95% CI, 1.06–1.38) and functional independence (RR, 1.14; 95% CI, 1.03–1.26) compared to no thrombolysis. Rates of sICH (RR, 1.46; 95% CI, 0.87–2.54) and mortality (RR, 1.07; 95% CI, 0.84–1.36) were similar between groups. Before EVT, Tenecteplase within 4.5 h was associated with greater disability reduction and higher functional independence compared with EVT alone; however, no benefit was observed beyond 4.5 h in those undergoing EVT. Among LVO patients not treated with EVT but with salvageable tissue on CT perfusion, Tenecteplase administered after 4.5 h was associated with improved functional outcomes.ConclusionIn this meta-analysis, Intravenous Tenecteplase was associated with improved outcomes when administered before EVT within 4.5 h and in the extended window, guided by advanced neuroimaging, among selected patients who lacked access to EVT.Systematic review registrationCRD420251115406.